Advances in contraceptive vaginal rings: what does the future hold?. (13th October 2018) - Monteiro, Ilza; Guazzelli, Cristina Falbo; Bahamondes, Luis
ABSTRACT: Introduction : Contraceptive vaginal rings (CVRs) are good contraceptive options because they do not require skilled providers, are self-administered, and show a higher stability of drug diffusion. Area covered : This article provides a review of the developments made with CVRs over the past number of years, while giving focus to the latest CVRs that have gone through clinical development. The author of the article also provides an expert perspective on the future of these useful therapeutic options. Expert opinion : Pharmacokinetic studies have shown that segesterone, an absorbable progestin that is used alone or in combination with ethinyl estradiol (EE) or E2, is the CVR of choice at this present time. Indeed, segesterone has demonstrated safety and efficacy as a CVR and is also an appropriate option for lactating women, as they are not absorbed orally. However, good cycle control is important for improved CVR adherence. CVRs that allow the combination of more than one drug may unravel another multi-purpose use when combined with microbicides and could provide combined protection to women who wish to protect themselves from pregnancy and sexually transmitted infection.